Development Modul Guided Inquiry Integrated Augmented Reality (M-GIIAR) to Improve Student’s Science Process Skills on Mechanical Wave Material - Nindyatami, Zulfi; Rochman, Chaerul; Chusni, Muhammad Minan (Physics Education Research Journal, 2024)
Science learning skills need to be applied at every stage of learning. However, students do not have good science process skills (SPS). Learning media is also needed to support modern and engaging science learning skills. Research using the ADDIE model, a sample of 30 students in class XI MIPA at SMAN 1 Wanayasa. The average validity test results are 82.40%. The results of implementing Authentic assessment based on Teaching and Learning Trajectory with Student Activity Sheets increased from each meeting; the average value was 85.58% with good effectiveness. The results of the N-Gain pretest and posttest based on the science process skills indicator obtained an average N-Gain result of 0.57 with a moderate interpretation. The researcher used a nonparametric hypothesis test with the Wilcoxon sign rank type. The results of the hypothesis test obtained acceptance of the alternative hypothesis (Ha), meaning that there was an increase experienced by students in SPS  in mechanical wave material. Based on several aspects, student responses obtained an average of 70.07% in the good and positive category.